Comparison of Different Implant Systems by Stress and Resistance of Prosthetic Screws: An Original Research - Pramod Punchiri Sadan (Wolters Kluwer Medknow Publications, 2024)
Introduction: For the best possible clinical results, dental implant systems must have their biomechanical characteristics thoroughly evaluated. These systems are essential to restorative dentistry. The purpose of this study was to analyze the resistance and stress distribution of prosthetic screws across five distinct implant systems. Methods: The stress distribution on prosthesis screws was evaluated, and loading conditions were simulated using finite element analysis (FEA). To assess the screws' resistance to torque forces, mechanical testing was done. Findings: Among the implant systems, there were notable differences in torque resistance and stress distribution. System A had the least amount of stress and the most torque resistance, whereas System E displayed the most stress and the least torque resistance. Conclusion: The results emphasize the significance of taking biomechanical characteristics into account when choosing implant systems for clinical usage, which has ramifications for patient care and treatment planning. Additional investigation concentrating on thorough clinical assessments is necessary to confirm these results and enhance treatment plans.